Studi Komunikasi Politik Legislator Perempuan Di DPRD Provinsi NTB - Hartin Nur Khusnia; Muhlis Muhlis; Tenri Waru (Universitas Mataram, 2018)
Equality of rights and obligations between men and women has been textually stated and guaranteed by various regulations, both at international, national and local levels. However, this guarantee does not necessarily guarantee equality between men and women to actively participate in practical politics. The fact that the representation of women in legislator of the West Nusa Tenggara Province is still low, which a total of 65 members of the Regional House of West Nusa Tenggara Province Representatives for the 2014-2016 periode 6 female legislators and 59 male legislators. The object of this research study is the political communication of women's legislators in the Regional House of Representatives of West Nusa Tenggara Province. The results of interviews with research informants can be concluded that the political communication of female legislators in the Regional House of Representatives of West Nusa Tenggara Province runs effectively because it is influenced by internal and external factors. Internal factors are the personal abilities of female politicians in building positive self-concepts. While external factors are participatory political culture in both the legislative and political parties where politicians take shelter. Political communication activities carried out by women's legislators aim to influence political policy, especially policies related to women's empowerment in West Nusa Tenggara. And aims to establish the self-image of politicians and institutions, both political parties or legislative bodies.Keywords: Political Communication, Women's Legislators, the Regional House of Representatives of West Nusa Tenggara Province